Improving Durability Of Milk Powder Storage By Adaptive Control Algoritm - Agung Kridoyono (Politeknik Harapan Bersama, 2018)
Milk powder is a processed product that the quality has been maintained by factory. Perishable product and easily reacting with other substances made milk easily changing the purity of milk. The effect of temperature, humidity, contact with other material, the growth of spore B. cereus and C. perfringens. The content of oxygen, peroxide numbers, water content so the effect is in the form of lumps, color changes and flecks of milk powder that can appear the green or gray colour in the milk powder. This paper studied the using of adaptive control algorithm on implementation of milk powder storage and serial interface to sent distributed data that can be saved in database, so the quality of milk powder still in a good condition even though the case is open or closed and the growth of bacteria can be controlled also the changes of milk powder condition can be monitored. The design can also be made for any type of milk powder media test because the control facility can be optimized on the system and record data can be stored in database. The result of this method the control not only inside in the media but also in outer box of storage media so the changes environment control on inner box more smooth with direct control and the effect of lump can be reduced.